Peran Distribusi Kekayaan Dalam Meningkatkan Kesejahteraan Publik: Pendekatan Ekonomi Mikro Syariah - Aini, Fauqah Nuri; Suryadi, Nanda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the role of wealth distribution in improving public welfare using an Islamic microeconomic approach. The research focuses on Islamic instruments of wealth distribution—zakat, infak (almsgiving), sadaqah (voluntary charity), and waqf (endowment)—and their contributions to socio-economic welfare. The method employed is qualitative descriptive research based on library studies, utilizing both classical and contemporary Islamic literature as well as relevant empirical sources. The findings reveal that Islamic wealth distribution mechanisms can effectively reduce economic inequality, strengthen social solidarity, and promote a more just and sustainable economic system. Zakat is proven effective in alleviating poverty, productive waqf provides long-term benefits through social asset management, while infak and sadaqah reinforce social networks and financial inclusion. The study recommends optimizing the management of zakat, waqf, infak, and sadaqah, expanding productive waqf through social investment, and increasing public literacy in Islamic economics. Greater collaboration among government bodies, zakat/waqf institutions, and the education sector is essential to ensure the effective and sustainable application of Islamic wealth distribution principles in the future.